Research on the Expression of Nationality in Chinese Piano Music - Jia , Li; Ho-Chung, Yeh (Journal of Roi Kaensarn Academi, 2024)
This paper focuses on the national expression of Chinese piano music, including the connotation of nationality, the development process of Chinese piano music, the main characteristics of Chinese piano music national expression and the development of Chinese piano music art suggestions. From the early 20th century to the present, Chinese piano music not only reflects the Times and composers of different personalities, but also reflects a clear common and continuity. Composers of various periods consciously explored and practiced the combination of western composition techniques and Chinese musical tradition, and paid attention to the artistic conception and connotation of Chinese culture in their piano works. Taking Nationality as the main line and constantly pursuing “Chinese style of piano music” is the main vein of the development and evolution of Chinese piano music, and the fundamental formation of Chinese piano music art style, which reflects the cultural identity consciousness of Chinese composers. Nationality has become a national cultural identity label of Chinese piano music in the world music art, which has gradually developed from a formal expression to a cultural expression. In the process of absorbing western composition theory and integrating into the essence of Chinese culture, Chinese piano music has gradually formed its own view of cultural identity, showing Nationality. Only when Chinese piano music goes to the world can it have the value of cultural development. On the road of future development, it needs to insist on the expression of Nationality in many aspects such as creation, publication, performance, teaching and academic research.